Improvement of Pulmonary Photodynamic Therapy: Nebulisation of Curcumin-Loaded Tetraether Liposomes - Jennifer Lehmann; Michael R. Agel; Konrad H. Engelhardt; Shashank R. Pinnapireddy; Sabine Agel; Lili Duse; Eduard Preis; Matthias Wojcik; Udo Bakowsky (MDPI AG, 2021)
Lung cancer is one of the most common causes for a high number of cancer related mortalities worldwide. Therefore, it is important to improve the therapy by finding new targets and developing convenient therapies. One of these novel non-invasive strategies is the combination of pulmonary delivered tetraether liposomes and photodynamic therapy. In this study, liposomal model formulations containing the photosensitiser curcumin were nebulised via two different technologies, vibrating-mesh nebulisation and air-jet nebulisation, and compared with each other. Particle size and ζ-potential of the liposomes were investigated using dynamic light scattering and laser Doppler anemometry, respectively. Furthermore, atomic force microscopy and transmission electron microscopy were used to determine the morphological characteristics. Using a twin glass impinger, suitable aerodynamic properties were observed, with the fine particle fraction of the aerosols being ≤62.7 ± 1.6%. In vitro irradiation experiments on lung carcinoma cells (A549) revealed an excellent cytotoxic response of the nebulised liposomes in which the stabilisation of the lipid bilayer was the determining factor. Internalisation of nebulised curcumin-loaded liposomes was visualised utilising confocal laser scanning microscopy. Based on these results, the pulmonary application of curcumin-loaded tetraether liposomes can be considered as a promising approach for the photodynamic therapy against lung cancer.